All nanoparticle-based P(MMA–AA)/TiO2 one-dimensional photonic crystal films with tunable structural colors. Issue 32 (3rd August 2017) - Wang, Lin; Zhang, Shufen; Lutkenhaus, Jodie L.; Chu, Lin; Tang, Bingtao; Li, Shuang; Ma, Wei
Abstract : All nanoparticle-based P(MMA–AA)/TiO2 1DPCs with functional structural colors were fabricated using an aqueous-based and environmentally friendly spin-assisted LbL process. Abstract : All nanoparticle-based poly(methyl methacrylate-acrylic acid) (P(MMA–AA))/TiO2 one-dimensional photonic crystals (1DPCs) with structural colors are designed and fabricated using an aqueous-based and environmentally friendly spin-assisted layer-by-layer (LbL) assembly. P(MMA–AA) nanoparticles with an average diameter of 37.3 nm are prepared in an aqueous solution using modified microemulsion polymerization, and are assembled with TiO2 nanoparticles with an average diameter of 26.8 nm. Easily tunable structural colors are achieved over a wide visible spectral range. The optical properties, including peak reflection position and intensity, of the 1DPCs are tuned by changing the Bragg stack number, the incident angles, and the thickness of the stacks. The obtained 1DPCs show rapid and distinguishable color changes upon exposure to acetone, chloroform, ethanol, and ethyl acetate vapors with good repeatability. More broadly, this fabrication method can also be used for assembling other functional polymer/inorganic hybrid 1DPCs for wide use.